Alkenone sea surface temperatures, delta13C and delta18O of G. ruber across sapropel intervals at ODP Sites 964 and 967, eastern Mediterranean Sea - Kay-Christian Emeis; Ulrich Struck (PANGAEA, 2022)
Organic carbon-rich sapropels formed in response to changes in the climatic background and in water mass circulation of the Mediterranean Sea. To examine the magnitude of change in surface waters, which are a prominent source of both deep and intermediate waters today, we measured the alkenone unsaturation index UK extquotesingle37 of sedimentary lipids (a sea-surface temperature proxy) and the stable carbon and oxygen isotope composition of planktonic foraminifer calcite at Ocean Drilling Project Sites 964 and 967 in closely spaced samples across sapropels. With these data we evaluated the temperature and salinity history of surface waters in the Ionian and Levantine Basins of the Eastern Mediterranean at times of sapropel deposition over the last 3 million years